Study on Conversion of Relative Soil Humidity to Volumetric Soil Water Content in China - LI Jiadi (Renmin Zhujiang)
In the absence of physical conversion parameters, this paper establishes the conversionmodel of relative soil humidity and volumetric soil water content by the regression analysismethod, and converts the observed data of relative soil humidity in China into the volumetric soilwater content. The results show that: There was a significant linear correlation between theobserved values of volumetric water content and relative humidity of soil in 33 of the 35coincident stationsat the same time, with the overall average correlation coefficient of 0.819 1.The error between converted value and observed value is very small. The mean relative error(MRE) of most stations and soil layers is within±5%, and the root mean square error (RMSE) isless than 5.0. In this method, the observed data of relative soil humidity in China from 1991 to2013 is converted into the volumetric soil moisture content, which expandes the time range of theobserved data of volumetric soil water content in China from 1981—1999 to 1981—2013.